Agrotourism Development Using Location Quotient Analysis in Cibuntu-Kuningan Village - Swantari, Anita; Ratnaningtyas, Heny; Festivalia, Filma (Institut Pariwisata Trisakti, 2021)
Cibuntu Village is a sub-district area that is one of the villages that has the potential for the development of the agricultural, plantation, and livestock sectors. In addition to these sectors, the tourism sector with the concept of agrotourism is expected to be developed and will make a significant contribution to the economy in Cibuntu Village. The purpose of this study is to determine the location of tourist attractions in Cibuntu Village and determine the types of tourism that can be developed in that location. The data analysis method used is divided into two parts, namely policy analysis and basic sector analysis using LQ (Location Quotient) calculation analysis. With applicable policy restrictions, tourism activities in Cibuntu Village are agrotourism and ecotourism. From the results of the LQ calculation, there are superior commodities, namely sweet potatoes, these commodities are worthy of investment to be developed in the future. Several alternative locations for tourism objects and activities that can be developed are agro-tourism activities in agricultural areas located in Cibuntu village which are designated as ecotourism areas. Keywords: Cibuntu Village Kuningan, Agrotourism, Location Quotient